Respuesta :
Since angle a + angle b = angle b + angle c, subtract b from both sides cancelling them and now you are left with angle a = angle c
Mop the floor hide the wet sign just to catch em slippin
It is proved that m∠C = m∠A for the given m∠A + m∠B = m∠B + m∠C.
What is subtraction?
Subtraction is a basic arithmetic operation where one number is reduced from another number.
We can prove the statement as shown below:
It is given that m∠A + m∠B = m∠B + m∠C.
Now we have to simplify the equation by removing like terms from both sides.
m∠A + m∠B = m∠B + m∠C
⇒ m∠A = m∠C
⇒ m∠C = m∠A
The like terms are removed from the LHS and RHS and this has helped us prove that m∠C = m∠A.
Therefore, we have proved that m∠C = m∠A for the given m∠A + m∠B = m∠B + m∠C.
Learn more about angles here: https://brainly.com/question/25716982
#SPJ2